2016
DOI: 10.1021/acs.chemmater.6b00850
|View full text |Cite
|
Sign up to set email alerts
|

Materials Design via Optimized Intramolecular Noncovalent Interactions for High-Performance Organic Semiconductors

Abstract: We report the design, synthesis, and implemention in semiconducting polymers of a novel head-to-head linkage containing the TRTOR (3-alkyl-3′-alkoxy-2,2′-bithiophene) donor subunit having a single strategically optimized, planarizing noncovalent S•••O interaction. Diverse complementary thermal, optical, electrochemical, X-ray scattering, electrical, photovoltaic, and electron microscopic characterization techniques are applied to establish structure−property correlations in a TRTOR-based polymer series. In com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 94 publications
3
107
0
Order By: Relevance
“…Among various nTs, terthiophene (3T) and tetrathiophene (4T) are highly promising ones . In order to improve solubilizing capability of 2T and achieve a high degree of coplanarity, we design a novel donor unit, the head‐to‐head linkage containing 3‐alkoxy‐3′‐alkyl‐2,2′‐bithiophene (TRTOR) . The TRTOR contains two solubilizing chains and has a high degree of coplanarity enabled by intramolecular sulfur–oxygen interaction .…”
Section: Methodsmentioning
confidence: 99%
“…Among various nTs, terthiophene (3T) and tetrathiophene (4T) are highly promising ones . In order to improve solubilizing capability of 2T and achieve a high degree of coplanarity, we design a novel donor unit, the head‐to‐head linkage containing 3‐alkoxy‐3′‐alkyl‐2,2′‐bithiophene (TRTOR) . The TRTOR contains two solubilizing chains and has a high degree of coplanarity enabled by intramolecular sulfur–oxygen interaction .…”
Section: Methodsmentioning
confidence: 99%
“…In an alternative approach, intramolecular non‐covalent interactions can be adopted to induce conformation lock and backbone planarization. For example, non‐covalent S…O coulomb attraction has been found between the sulfur of thienyl unit and the oxygen of alkoxyl or carbonyl substituents on adjacent aromatics, and was utilized in the design of a variety of conjugated polymers and small molecular semiconductors . Most of the works demonstrated that such non‐covalent S…O interactions can improve the material performance and achieve a PCE over 9.39% and mobility higher than 5.37 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent interactions play ak ey role in several biological [1] and technological processes, [2][3][4][5] yet their characterization and interpretation are still far from being satisfactory,especially when the bonding pair is made up of two nonhydrogen atoms.I nt his connection, integrated experimental and computational investigations can play an invaluable role provided that the accuracy of the results is accompanied by their rigorous and understandable interpretation. Different quantum chemical models (NOCV/CD and NBO) agree in indicating that this interaction largely prevails over the C À H···O and CÀH···N hydrogen bonds.F urthermore,aSAPT analysis shows that electrostatic and dispersion interactions play ac omparable role in stabilizing the complex.…”
mentioning
confidence: 99%
“…Different quantum chemical models (NOCV/CD and NBO) agree in indicating that this interaction largely prevails over the C À H···O and CÀH···N hydrogen bonds.F urthermore,aSAPT analysis shows that electrostatic and dispersion interactions play ac omparable role in stabilizing the complex. The conformational landscape exploration and stationary points characterization have been performed using state-of-the-art quantum-chemical computations providing significant insights on structure determination.Noncovalent interactions play ak ey role in several biological [1] and technological processes, [2][3][4][5] yet their characterization and interpretation are still far from being satisfactory,especially when the bonding pair is made up of two nonhydrogen atoms.I nt his connection, integrated experimental and computational investigations can play an invaluable role provided that the accuracy of the results is accompanied by their rigorous and understandable interpretation. Along with the well-established hydrogen and halogen bonds,e merging classes of noncovalent interactions are attracting increasing attention, such as the R À X···Y ones involving apnicogen atom (X = N, P, As,SborBi), [6] with RÀXand Ybeing the pnicogen bond donor and acceptor,r espectively,i na nalogy with hydrogen [7] and halogen bond definitions.…”
mentioning
confidence: 99%